Inflation Stabilization and Economic Transformation in Poland : The First Year - Lane, Timothy (IMF Working Papers; Working Paper, 1991)
This paper reviews the experience of 1990, the first year of Poland's program of stabilization and reform. The background is described, including previous reform efforts and the crisis of the late 1980s. Then the various elements of the program are discussed, including fiscal adjustment, wage controls, the possibility of an initial liquidity overhang, the exchange rate anchor, and structural reforms. The initial results of the program are assessed, and alternative explanations of the decline in output are considered.